MiRNA-532-5p Regulates CUMS-Induced Depression-Like Behaviors and Modulates LPS-Induced Proinflammatory Cytokine Signaling by Targeting STAT3 - Yan X (Dove Medical Press, 2020)
Xue Yan,* Dehao Zeng,* He Zhu, Yijing Zhang, Yuying Shi, Yingxiu Wu, Hongmei Tang, Detang Li Pharmaceutical Department, The First Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province 510405, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xue Yan Tel +86-020-36598864Email zd0171@163.comBackground: It is known that miR-532-5p is critical for neuronal differentiation. However, the role of miR-532-5p in depression remains unknown. This study aimed to investigate the role and mechanism of miR-532-5p in major depressive disorder (MDD).Methods: The depression mice model was established by chronic unpredictable mild stress (CUMS) and confirmed by forced swimming test (FST) and sucrose preference test (SPT). The role of miR-532-5p in MDD was detected by tail suspension test (TST), FST, SPT and SIT. QRT-PCR was used to detect the expression of miR-139-5p in hippocampus and BV-2 microglia of mice. ELISA and Western blotting were used to detect the expression of the nitric oxide synthase (NOS), proinflammatory cytokines (IL-6, IL-1β, TNF-α, and MCP-1) and transcriptional activator 3 (STAT3). Luciferase reporter assay was used to verify the downstream target genes of miR-532-5p.Results: MiR-532-5p was significantly reduced in the hippocampus of mice treated with CUMS. Overexpression of miR-532-5p significantly reduced CUMS-induced depression-like behaviors and suppressed the expression of IL-6, IL-1β, TNF-α and MCP-1. MiR-532-5p directly targeted signal transducers and STAT3 in BV2 cells. In addition, overexpression of miR-532-5p restrained the raise of inducible NOS and IL-6, IL-1 β, TNF-α and MCP-1 in LPS-exposed BV2 cells.Conclusion: This study indicates that miR-532-5p plays an important role in CUMS-induced depression-like behaviors by targeting STAT3, and miR-532-5p may be a potential target for MDD therapy.Keywords: miR-532-5p, STAT3, major depressive disorder, inflammation